MEDB-55. Single-cell transcriptomics reveals progenitor cells expressing a photoreceptor program as putative cells origin of MYC-driven Group 3 Medulloblastoma. (3rd June 2022) - Zhao, Miao; Mainwaring, Oliver; Rosén, Gabriela; Elgendy, Ramy; Doroszko, Milena; Rijpkema, Sanne; Sundstrom, Anders; Nelander, Sven; Weishaupt, Holger; Furukawa, Takahisa; Swartling, Fredrik J
Abstract: Brain tumors are the leading cause of childhood cancer-related death. Medulloblastoma is the most common malignant pediatric brain tumor with about 70% survival. Medulloblastoma comprises four distinct subgroups respective of genomic and molecular drivers influencing tumorigenesis. It has been established that despite being considered a single disease entity, each subgroup arises from a distinct population of cells found within unique compartments of the developing brain. The cell of origin of Group 3 medulloblastoma, the most malignant medulloblastoma subgroups, is currently unknown and remains controversial. Transcriptional profiling has revealed that Group 3 medulloblastomas are characterized by elevated expression of a photoreceptor program, which has not been described in the normal cerebellar development but is well characterized in the developing pineal gland and retinal. By investigating and comparing brain and tumor development between our previously developed medulloblastoma mice model (GMYC), where mice spontaneously develop Group 3 medulloblastoma after 4-6 months of age, and their control counterparts, we found that tumor cells emerged from progenitor cells where MYC overexpression drove the transformation of immature progenitor cells expressing a photoreceptor program. Our data suggest that MYC-driven Group 3 medulloblastoma originates from progenitor cells expressing a photoreceptor program, which has implications for future research and the development of novel treatments targeting this devastating childhood malignancy.